Pemberian Upah Kerja Lembur Pada PT. Permodalan Nasional Madani Cabang Kota Baru Jambi - Restia, Chandra; Muskibah, Muskibah (Universitas Jambi, Fakultas Hukum, 2024)
This research aims to determine and analyze legal protection for overtime wages at PT. Madani National Capital (PNM) Kota Baru Jambi Branch, and to find out and analyze what obstacles cause non-payment of overtime wages at PT. Madani National Capital (PNM) Kota Baru Jambi Branch. The problem in this research is: How is the legal protection for overtime wages at PT. Madani National Capital (PNM) Kota Baru Jambi Branch?, and what are the obstacles causing non-payment of overtime wages at PT. Madani National Capital (PNM) Kota Baru Jambi Branch?, The research method is Empirical Juridical combining legal materials (secondary data) with primary data obtained on legal facts that occurred between workers and PT. Madani National Capital City New Branch. The results of the research are the implementation of the rights and obligations of parties in the cooperation agreement between workers and PT. Madani National Capital City Baru Branch has not been implemented in accordance with the provisions of the Law on Wages, the Employment Law and the agreement, where the core point of the agreement is that workers who work at PT. Civil National Capital must be paid wages in accordance with the Law on Wages and the Employment Law as well as the work contract agreement that has been agreed upon by both parties. The obstacles faced by these workers are that their wages do not match expectations, there is overtime pay that is not given to workers by PT. Civil National Capital.